Pentobarbital Anesthesia Suppresses the Glucose Response to Acute Intermittent Hypoxia in Rat - Nedoboy, Polina E.; Houlahan, Callum B.; Farnham, Melissa M. J. (Frontiers in Physiology, 2021)
A key feature of sleep disordered breathing syndromes, such as obstructive sleep apnea is intermittent hypoxia. Intermittent hypoxia is well accepted to drive the sympathoexcitation that is frequently associated with hypertension and diabetes, with measurable effects after just 1hr. The aim of this study was to directly measure the sympathetic and glucose response to 1hr of acute intermittent hypoxia in pentobarbital anesthetized rats. However, we found that while a glucose response is measurable in conscious rats exposed to intermittent hypoxia, it is suppressed in anesthetized rats. Intermittent hypoxia for 1, 2 or 8hr increased blood glucose by 0.7 ± 0.1 mmol/L in conscious rats but had no effect in anesthetized rats (-0.1 ±_0.2 mmol/L). These results were independent of the frequency of the hypoxia challenges, fasting state, vagotomy, or paralytic agents. A supraphysiological challenge of 3min of hypoxia was able to induce to glycemic response indicating that the reflex response is suppressed, not abolished under pentobarbital anesthesia. We conclude that pentobarbital anesthesia is unsuitable for investigations into glycemic response pathways in response to intermittent hypoxia in rats.